2012
DOI: 10.1186/1757-1146-5-29
|View full text |Cite
|
Sign up to set email alerts
|

Importance and challenges of measuring intrinsic foot muscle strength

Abstract: BackgroundIntrinsic foot muscle weakness has been implicated in a range of foot deformities and disorders. However, to establish a relationship between intrinsic muscle weakness and foot pathology, an objective measure of intrinsic muscle strength is needed. The aim of this review was to provide an overview of the anatomy and role of intrinsic foot muscles, implications of intrinsic weakness and evaluate the different methods used to measure intrinsic foot muscle strength.MethodLiterature was sourced from data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 94 publications
(358 reference statements)
1
115
0
1
Order By: Relevance
“…The authors 24 also found a longer time to peak T2 signal intensity in elderly participants (157.1 6 109.9 seconds) than in younger ones (95.1 6 77.6 seconds), suggesting that age may influence T2 peaks and the time to return to baseline. Heat mapping through T2 percentage-activation change has shown 25 varying activation levels in the medial gastrocnemius (13.3% 6 1.3%), lateral gastrocnemius (7.8% 6 1.2%), and soleus (6.3% 6 2.1%) after unilateral heel raises, which are comparable to the percentage increases in the intrinsic plantar foot muscles in our study. Emerging evidence has shown that for T2, higher-intensity exercises result in a quicker rate of change 26 as well as a larger overall increase 21 when compared with lower-intensity exercises.…”
Section: Discussionsupporting
confidence: 87%
“…The authors 24 also found a longer time to peak T2 signal intensity in elderly participants (157.1 6 109.9 seconds) than in younger ones (95.1 6 77.6 seconds), suggesting that age may influence T2 peaks and the time to return to baseline. Heat mapping through T2 percentage-activation change has shown 25 varying activation levels in the medial gastrocnemius (13.3% 6 1.3%), lateral gastrocnemius (7.8% 6 1.2%), and soleus (6.3% 6 2.1%) after unilateral heel raises, which are comparable to the percentage increases in the intrinsic plantar foot muscles in our study. Emerging evidence has shown that for T2, higher-intensity exercises result in a quicker rate of change 26 as well as a larger overall increase 21 when compared with lower-intensity exercises.…”
Section: Discussionsupporting
confidence: 87%
“…The reliability of different ultrasound based measurements was reported in the literature: intra and inter-rater reliability of dynamic compression of the heel pad [38]; dorso-plantar thickness, medio-lateral width and CSA of AbdH [39], thickness and CSA of FHB, FDB, flexor hallucis longus (FHL), quadratus plantae (QP), AbdM, quadratus plantae (PER); thickness of tibialis anterior (TA) and PF [9,28]; fascicle length and pennation angle of MG and TA [40], hypoechoic rims around tendons, joint spaces, erosions, cartilage thickness [10]. However, ultrasonography remains a highly operator-dependent technique [9].…”
Section: Ultrasonography Used To Evaluate the Tissue's Structural Chamentioning
confidence: 99%
“…However, ultrasonography remains a highly operator-dependent technique [9]. Seen from the perspective of tissue stress theory, there are not at this moment a large number of articles which have used ultrasound methods for evaluating the effectiveness of foot orthotics.…”
Section: Ultrasonography Used To Evaluate the Tissue's Structural Chamentioning
confidence: 99%
See 2 more Smart Citations